Oxidative State in Cutaneous Melanoma Progression: A Question of Balance - Mascia Benedusi; Heaji Lee; Yunsook Lim; Giuseppe Valacchi (MDPI AG, 2024)
Reactive oxygen species (ROS) are highly bioactive molecules involved not only in tissue physiology but also in the development of different human conditions, including premature aging, cardiovascular pathologies, neurological and neurodegenerative disorders, inflammatory diseases, and cancer. Among the different human tumors, cutaneous melanoma, the most aggressive and lethal form of skin cancer, is undoubtedly one of the most well-known "ROS-driven tumor", of which one of the main causes is represented by ultraviolet (UV) rays' exposure. Although the role of excessive ROS production in melanoma development in pro-tumorigenic cell fate is now well established, little is known about its contribution to the progression of the melanoma metastatic process. Increasing evidence suggests a dual role of ROS in melanoma progression: excessive ROS production may enhance cellular growth and promote therapeutic resistance, but at the same time, it can also have cytotoxic effects on cancer cells, inducing their apoptosis. In this context, the aim of the present work was to focus on the relationship between cell redox state and the signaling pathways directly involved in the metastatic processes. In addition, oxidative or antioxidant therapeutic strategies for metastatic melanoma were also reviewed and discussed.